2004
DOI: 10.1097/01.brs.0000142007.38256.7f
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations of Treatment for Back Pain

Abstract: Patients have explicit expectations on diagnosis, instructions, and interpersonal management. New strategies need to be developed in order to meet patients' expectations better. Practice guidelines should pay more attention to the best way of discussing the causes and diagnosis with the patient and should involve them in the decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(103 citation statements)
references
References 51 publications
6
89
0
3
Order By: Relevance
“…The review reported that there were two 'treatment aspects' (p. 2310) 194 that occurred most frequently. These were that (i) patients want to know the cause of their pain and (ii) patients want information or instruction.…”
Section: Support For Self-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The review reported that there were two 'treatment aspects' (p. 2310) 194 that occurred most frequently. These were that (i) patients want to know the cause of their pain and (ii) patients want information or instruction.…”
Section: Support For Self-managementmentioning
confidence: 99%
“…l Self-management support needs to address 'noncongruence' (p. 2313) 194 between patients and professionals. This includes differences in opinions about the definition and cause of LBP and how it should be identified and treated.…”
Section: Support For Self-managementmentioning
confidence: 99%
“…Potentially a referral for imaging is a procedure that health care providers view as providing reassurance that no serious pathology exists and justification for providing advice to staying active through the period of pain. In a study on patients' expectations and satisfaction, the unenviable position of the health care providers was underlined: on the one hand guidelines recommend refraining from imaging examination on nonspecific LBP while patients often have expectations about finding an exact cause of the pain (21).…”
Section: Discussionmentioning
confidence: 99%
“…Zudem helfen klare Absprachen über das gestufte, an abgesprochenen Kriterien orientierte Vorgehen und der Einbezug des Patienten in die Entscheidungsprozesse. Da die Erwartungen der Schmerzpatienten in der Regel zunächst primär die somatische Einordnung ihrer Beschwerden wie auch die grundlegende Anerkenntnis ihrer Schmerzen betreffen, trägt es zur Erhö-hung der Motivation bei, wenn dieser Erwartung insbesondere am Anfang der Behandlung entsprochen wird [46].…”
Section: Therapiemotivationunclassified